2020
DOI: 10.1186/s13071-020-3890-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Blastocystis in kindergarten children in southern Xinjiang, China

Abstract: Background: Blastocystis is one of the most common intestinal parasites in humans and various animals worldwide. Few studies are available regarding the genetic characterization of Blastocystis infections in humans in China. Methods: In the present study, 609 fecal samples were collected from two-to six-year-old kindergarten children in southern Xinjiang and were examined by polymerase chain reaction (PCR). Results: The infection rate of Blastocystis was 14.3% (87/609); no significant difference was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…To date, six Blastocystis subtypes (ST1 to ST6) have been identified in humans in China, and ST3 is the most dominant subtype. 21 In this study, four subtypes (ST1 to ST4) were characterized in 48 Blastocystis isolates, and ST3 was found to be the dominant subtype, which was in agreement with the findings from the same province, 22,26,27 and the isolates from kindergarten children in southern Xinjiang, northwestern China 42 and college students in Guangxi, northern China, 43 as well as from Zhejiang province and Shanghai municipality, eastern China. 27 However, ST1 was also reported as the dominant Blastocystis subtype in China.…”
Section: Discussionsupporting
confidence: 86%
“…To date, six Blastocystis subtypes (ST1 to ST6) have been identified in humans in China, and ST3 is the most dominant subtype. 21 In this study, four subtypes (ST1 to ST4) were characterized in 48 Blastocystis isolates, and ST3 was found to be the dominant subtype, which was in agreement with the findings from the same province, 22,26,27 and the isolates from kindergarten children in southern Xinjiang, northwestern China 42 and college students in Guangxi, northern China, 43 as well as from Zhejiang province and Shanghai municipality, eastern China. 27 However, ST1 was also reported as the dominant Blastocystis subtype in China.…”
Section: Discussionsupporting
confidence: 86%
“…For comparison, very few studies have previously focused on the intra-ST genetic diversity among these three major STs and almost all were based on the analysis of sequences from another domain of the SSU rDNA gene than the one targeted in our study [ 18 , 40 ]. Through the analysis of this second marker, it was also reported that genetic diversity could vary dramatically at the intra-ST level in epidemiological surveys conducted for instance in China [ 58 ] and Nigeria [ 37 ]. Indeed, ST2 was shown to exhibit the greater intra-ST diversity (average of 2.2 isolates per genotype) followed by ST1 (6.7) then ST3 (21.5) in the Chinese study.…”
Section: Discussionmentioning
confidence: 99%
“…infecting rats, subtype ST4 was the most prevalent. Besides in rodents, subtype ST4 is one of the most common subtypes found in humans [14]. Similarly, subtype ST4 has also been reported in non-human primates, giraffes, kangaroos, dogs, snow leopards, and ostriches [2,15,16,21,23].…”
Section: Resultsmentioning
confidence: 75%